2022
DOI: 10.1097/ncc.0000000000001149
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Control Study of the Effects of Turmeric Mouthwash on Oral Health Status, Treatment-Induced Mucositis, and Associated Oral Dysfunctions Among Patients With Head and Neck Cancer

Abstract: BackgroundOral mucositis is the most severe and debilitating adverse effect of cancer treatment, resulting in inadequate nutritional intake, treatment disruptions, and dose alteration, leading to increased hospital costs and decreased tumor control.ObjectiveThe aim of this study was to determine the effectiveness of turmeric mouthwash on oral health status and onset and severity of treatment-induced oral mucositis and associated oral dysfunctions among head and neck cancer patients.MethodsA randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…However, at the 3-week follow-up visit, the results changed. After removing the articles of Delavarian et al, 2019, Arun et al, 2020Thomas 2023, no significant difference was observed. Similarly, at the 4-week follow-up visit, the result changed when the article by Shah et al was removed.…”
Section: Sensitivity Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…However, at the 3-week follow-up visit, the results changed. After removing the articles of Delavarian et al, 2019, Arun et al, 2020Thomas 2023, no significant difference was observed. Similarly, at the 4-week follow-up visit, the result changed when the article by Shah et al was removed.…”
Section: Sensitivity Analysismentioning
confidence: 89%
“…Various treatment types of turmeric have been designed to improve oral mucositis, and they include mouthwash, gel, and other oral treatments (Charantimath, 2016;Shah et al, 2020;Kia et al, 2021;Soni et al, 2022;Thomas et al, 2023). However, the previous metaanalyses did not consider the differences between various treatment types (Dharman et al, 2021;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations